2016
DOI: 10.5483/bmbrep.2016.49.5.187
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors attenuated cholesterol-induced cardiac hypertrophy in H9c2 cells

Abstract: The Ubiquitin proteasome system (UPS) plays roles in protein degradation, cell cycle control, and growth and inflammatory cell signaling. Dysfunction of UPS in cardiac diseases has been seen in many studies. Cholesterol acts as an inducer of cardiac hypertrophy. In this study, the effect of proteasome inhibitors on the cholesterol-induced hypertrophic growth in H9c2 cells is examined in order to observe whether UPS is involved in cardiac hypertrophy. The treatment of proteasome inhibitors MG132 and Bortezomib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Lee et al found that treatment with proteasome inhibitors, namely, MG132 and bortezomib, for 24 h regressed cardiac hypertrophy induced by cholesterol in H9c2 cells [7]. In the pressure overload-induced cardiac hypertrophic rat model, proteasome inhibition clearly attenuated cardiac fibrosis and heart failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al found that treatment with proteasome inhibitors, namely, MG132 and bortezomib, for 24 h regressed cardiac hypertrophy induced by cholesterol in H9c2 cells [7]. In the pressure overload-induced cardiac hypertrophic rat model, proteasome inhibition clearly attenuated cardiac fibrosis and heart failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Treating mouse models using epoxomicin, an irreversible proteasome inhibitor attenuated the development of cardiac hypertrophy after transverse aortic constriction (TAC)-induced short-term pressure overload ( Depre et al, 2006 ; Hedhli et al, 2008 ; Hedhli and Depre, 2009 ), similarly, genetically modified homozygous Mybpc3 -targeted knock-in (KI) mice showed slight improvement in cardiac function after epoxomicin treatment ( Schlossarek et al, 2014b ). Low doses of another proteasome inhibitor MG132 suppressed isoproterenol- induced hypertrophy evident by reduction in induction of various hypertrophic markers such as, BNP, β-MHC, and SM α-actin as well as suppression of key signaling molecules such as Akt, calcineurin and ERK1/2 ( Meiners et al, 2008 ), which may the reason of the suppressed hypertrophy as demonstrated by many studies both in vivo and in vitro ( Sugden, 1999 ; Shioi et al, 2000 ; Bueno et al, 2002 ; Maillet et al, 2013 ; Bian et al, 2014 ; Jiang et al, 2015 ; Lee et al, 2016 ). Chen et al (2010) inferred using long-term treatment of MG132 that an alleviated cardiac hypertrophy in AAB rats is a result of activation of ERK1/2 and JNK1 signaling pathways without affecting blood pressure.…”
Section: Potential Therapeutic Ups Interventions In Cardiac Hypertropmentioning
confidence: 99%
“…Ang II-induced hypertensive models showed inhibited hypertrophic phenotype via stabilizing Ang II type 1 receptor-associated protein (ATRAP) and inactivation of the p38 MAPK and STAT3 signaling pathways when treated with bortezomib, however, of the study didn’t extend to in vivo analysis ( Li N. et al, 2015 ). Likewise, proteasome inhibitors MG132 and bortezomib suppressed cardiac hypertrophy induced by cholesterol and decreased expression of hypertrophic marker genes by inhibiting ERK and Akt activation ( Lee et al, 2016 ). Treatment with the irreversible proteasome inhibitor PS-519 significantly prevented the development and promoted its regression of isoprenaline-induced hypertrophy by blocking the IκB-degradation effectively preventing nuclear translocation and activation of NF-κB in mice ( Table 2 ) ( Stansfield et al, 2008 ).…”
Section: Potential Therapeutic Ups Interventions In Cardiac Hypertropmentioning
confidence: 99%
“…The physiopathology of hypertension includes several factors: a more activated renin-angiotensin-aldosterone system (RAAS) and stimulated sympathetic nervous system [59]. Both the processes mediate the pressure of blood, sodium intake, potassium removal from the body, and vasoconstriction (Muñoz-Durango et al, 2016).…”
Section: Hypertensionmentioning
confidence: 99%